Analisis Rasio Keuangan Mengunakan Rasio Likuiditas, Profitabilitas Dan Solvabilitas Untuk Menilai Kinerja Keuangan Pada KSP Kopdit Obor Mas - Maria Selviana Runu; Andreas Rengga; Konstantinus Pati Sanga (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2023)
The background of this research was conducted to determine the financial performance of Obor Mas Credit Union by using Liquidity Ratio, Profitability Ratio, and Solvency Ratio by analyzing its financial statements. The populations in this research were yhe financial statements of Obor Mas Credit Union, while the sample in this research was the financial statements of Obor Mas Credit Union in 2018-2022. This research was categorized as quantitative research using a descriptive study. The result showed that based on the level of liquidity ratios as measured by the current ratio, quick ratio, and cash ratio in 2018-2019, overall was good because the result were above the average performance standars set by the credit union, namely the current ratio of 232.80% ≥125, cash ratio of 28.87% ≥ 20%, and quick ratio of 232.63% ≥ 90. The profitability ratio in 2018-2019 overall was not good (problematic) because the average was less than the performance standards set by the credit union, namely return on equity 1.74% < 5 and return on asset 0.46% < 3. The solvency ratio, as measured by the total debt to own capital in 2018-2022 was good because the average was above the performance standars set by the credit union, namely 280.10%. The total debt ratio to total assets in 2018 was good because the average was above the performance standars set by the credit union, namely 73.54%.